Reading Public Romanticism. - Magnuson, Paul. (Princeton : Princeton University Press, 2014)
Reading Public Romanticism is a significant new example of the linking of esthetics and historical criticism. Here Paul Magnuson locates Romantic poetry within a public discourse that combines politics and esthetics, nationalism and domesticity, sexuality and morality, law and legitimacy. Building on his well-regarded previous work, Magnuson practices a methodology of close historical reading by identifying precise versions of poems, reading their rhetoric of allusion and quotation in the contexts of their original publication, and describing their public genres, such as the letter.
Acknowledgments ; Abbreviations and Key Words ; INTRODUCTION; CHAPTER ONE ; The Corresponding Society: The Public Discourse; CHAPTER TWO ; The Corresponding Society: Reading the Correspondence; CHAPTER THREE ; The Politics of ""Frost at Midnight""; CHAPTER FOUR ; The Mariner's Extravagance and the Tempests of Lyrical Ballads; CHAPTER FIVE ; The Dedication of Don Juan; CHAPTER SIX; Keats's ""Leaf-Fringed Legend""; Index.
Print version record.
Keywords: English poetry -- 19th century -- History and criticism; Literature and society -- Great Britain -- History -- 19th century; Authors and readers -- Great Britain -- History -- 19th century; English poetry -- 18th century -- History and criticism; Public opinion -- Great Britain -- History -- 19th century; Public opinion -- Great Britain -- History -- 18th century; Literary form -- History -- 18th century; Literary form -- History -- 19th century; Public opinion in literature; Romanticism -- Great Britain; Speech acts (Linguistics); LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; POETRY -- English, Irish, Scottish, Welsh; Authors and readers; English poetry; Literary form; Literature and society; Public opinion; Public opinion in literature; Romanticism; Speech acts (Linguistics); Great Britain; 1700-1899; Electronic books; 7 -- Electronic books; Criticism, interpretation, etc; History